MODEL PEMBELAJARAN KOOPERATIF PENGAJARAN BAHASA ARAB - Muhlis, Achmad (STAIN PAMEKASAN, 2011)
Co-operative study represents learnig strategy with a number of students as small group member which its ability level differs of each other either from side of maharah al-lughawiyah and also âanashir al-lughah . This study is one of study models where students learn and work in groups having the character of heterogeneous. Learning efficacy from group is depended on group member ability and activity , either through individually and also group. This research tries to elaborate co-operative study at station of Arab language in pesantren maisonette of Sumenep annuqayah, as one of the alternative of study model in each maharah also anashir al-lughawiyah.